Microstructure and compression resistance of bean goose (Anser fabalis) feather shaft. Issue 2 (29th October 2019) - Zou, Meng; Xu, Lihan; Zhou, Jianfei; Song, Jiafeng; Liu, Shengfu; Li, Xiujuan
Abstract: The bean goose Anser fabalis, noted for its excellent flying ability, has feathers composed of keratinized products derived from epidermal cells, which play a crucial role in flight. The feather shaft is an important connective unit, made of a lightweight material, which also contributes to aiding flight. The shaft can withstand loads from different directions and has outstanding compression resistance. In this study, the microstructure and composition of the A. fabalis feather shaft were observed by scanning electron microscopy and Fourier transform infrared spectrometry, and its compression resistance was studied by compression testing. The results indicated that the mechanical property of the shaft is related to its microstructure. Compression testing verified that the primary feathers had the strongest mechanical properties, followed by the secondaries, and finally the alulae. Under the same conditions, the specific energy absorption of the three feather types was 5.96, 5.02, and 3.17 J/g, respectively. With increasing moisture content, the rachis was softened and the energy absorption was reduced. At low moisture content, the specific energy absorption of the primaries was reduced to 1.03 J/g, that of the secondaries was reduced to 1.72 J/g, and that of the alulae to 0.39 J/g. The feather shafts have the advantage of light weight while maintaining the required mechanical properties. These results provide a theoretical and experimental basis for crashworthiness in bionic designs based on the requirements of light weight. Abstract : 1. The configuration, structure, material characters, and compression resistance of the A. fabalis feather shaft were investigated. 2. There are differences in compression resistance of feather shafts from different parts of the body of A. fabalis . 3. The A. fabalis feather shafts with lower water content had higher compressive strength and better energy absorption.